Digital marketing strategies and their impact on the sustainable growth of micro and small businesses: case analysis - Cahui Torres, Licely Patricia (2022)
This research shows relevant information to get into the current situation of MSMEs in Latin America, regarding the use of digital marketing strategies. The interest in exploring this topic is due to the relevance of the use of digital media, since currently many micro and small businesses are still afraid to enter these areas, because they have limited knowledge of their properties and management. This research seeks to promote the continued adoption of these digital tools, by applying appropriate e-marketing solutions to ensure the sustained success of the business over time and thus be prepared to face the challenges of the environment. For the selection of the bibliographic sources different filtering was used, specifying to choose researches according to our study topic that have been published from the year 2016 to the year 2021. At the end of this process, a total of 12 indexed journal articles, 2 undergraduate theses and 1 book were obtained. According to the results found, it can be observed that, in most of the countries analyzed, large companies are the ones that have obtained the best and greatest benefit from digital marketing, on the other hand, micro and small companies have not yet been able to efficiently apply this type of digital tools, due to the degree of ignorance of these and also because of the scarcity of their budget.